“Propuesta de un Plan de Marketing para la Panadería y Pastelería Dulce Paladar en la ciudad de Quito, provincia de Pichincha” - Collaguazo Saritama, Junnior Marco (2024)
The main purpose of this academic research is to propose a Marketing Plan for the bakery and pastry shop Dulce Paladar in the city of Quito, province of Pichincha, the methods used were: descriptive, inductive, deductive and statistical method; as for the techniques used are the interview, observation and survey of internal and external customers. To carry out the internal analysis of the bakery where the strengths and weaknesses were identified, an interview with the owner was carried out, a survey of key informants, these were an internal customer and 83 external customers, which when carrying out their respective weighting of factors in the EFI matrix, a result of 2.52 was determined, which means that the strengths predominate over the weaknesses. To identify the opportunities and threats, an external diagnosis was carried out based on Pestel analysis and Porter's 5 forces, and the factors were weighted using the EFE matrix, giving a result of 2.52, which means that the opportunities prevail over the threats. Through the SWOT analysis the high impact matrix was constructed with which it was possible to cross factors to determine the strategies called FO, DA, DO, FA which served to define 5 strategic objectives containing its problem, goal, policy, responsible, activities and a budget of $ 733.8 dollars, item necessary to carry out its implementation, in this way it was intended to give formality to the proposals put forward.